Impaired diastolic function and elevated Nt-proBNP levels in type 1 diabetic patients without overt cardiovascular disease - YAVUZ, DİLEK (SPRINGER-VERLAG ITALIA SRL, 2013)
Diabetic cardiomyopathy is an important complication of type 1 diabetes mellitus. Diastolic heart failure is an early manifestation of diabetic cardiac disease. Nt-proBNP is a valuable marker of ventricular dysfunction. The aim of this study was to determine Nt-proBNP concentrations in type 1 diabetic patients and determine their relationship with ventricular diastolic dysfunction (DD) and carotid artery intima media thickness (CIMT) measurements. Sixty-seven type 1 diabetic patients (30.2 +/- A 8.0 years; W/M: 24/43) without known cardiovascular disease and 48 healthy controls (30.5 +/- A 6.4 years; W/M: 19/29) were recruited. Nt-proBNP levels were measured. Conventional and tissue Doppler echocardiography were used to evaluate left ventricular diastolic function and CIMT. Nt-proBNP in diabetic patients was significantly higher than in controls (38 +/- A 34.8 vs. 15.1 +/- A 12.7 pg/ml) (P = 0.004). E-a level was higher (12.3 +/- A 3 vs. 10.3 +/- A 4 cm/s, P = 0.003) and E/E-a ratio was lower in patients (6.6 +/- A 2.5 vs. 9.7 +/- A 5.9, P = 0.001) compared with controls. Ratio of DD was higher in patients than controls (11.1 vs. 2.1%, P = 0.01). CIMT measurements in diabetic patients were higher than controls (0.54 +/- A 0.11 vs. 0.48 +/- A 0.05 mm, P = 0.02). Logistic regression revealed age and HbA1c to be independently associated with the presence of DD. Nt-proBNP levels are elevated in type 1 diabetic patients without overt cardiovascular disease and the presence of DD is increased in diabetic patients in comparison with controls. Nt-proBNP levels do not seem to be related to the presence of DD and subclinical atherosclerosis in this group of patients.
Keywords: Left ventricular diastolic dysfunction; Nt-pro BNP; Carotid intima media thickness; Type 1 diabetes mellitus; LEFT-VENTRICULAR DYSFUNCTION; BRAIN NATRIURETIC PEPTIDE; TISSUE DOPPLER; PLASMA-LEVELS; UTILITY; BNP; ECHOCARDIOGRAPHY; ABNORMALITIES; CARDIOMYOPATHY; QUANTITATION